2017
DOI: 10.1186/s10194-017-0724-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulated airplane headache: a proxy towards identification of underlying mechanisms

Abstract: BackgroundAirplane Headache (AH) occurs during flights and often appears as an intense, short lasting headache during take-off or landing. Reports are limited on pathological mechanisms underlying the occurrence of this headache. Proper diagnosis and treatments would benefit from identification of potential pathways involved in AH pathogenesis. This study aimed at providing a simulated airplane headache condition as a proxy towards identification of its underlying mechanisms.MethodsFourteen participants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(70 citation statements)
references
References 39 publications
1
68
1
Order By: Relevance
“…Headache attributed to airplane travel (airplane headache (AH)) is a painful headache that occurs during the takeoff and/ or landing; however, the headache mostly appears during the landing [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is still uncertainty about the treatment of AH, but the current literature indicates that pharmacological treatments such as triptans might be effective for AH [4].…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Headache attributed to airplane travel (airplane headache (AH)) is a painful headache that occurs during the takeoff and/ or landing; however, the headache mostly appears during the landing [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is still uncertainty about the treatment of AH, but the current literature indicates that pharmacological treatments such as triptans might be effective for AH [4].…”
Section: To the Editormentioning
confidence: 99%
“…After these two AH attacks, he contacted the GP as the headache pain was so severe that he decided not to fly anymore unless the doctor could find a solution for him. Afterwards, he requested a referral to a neurologist where he brought the AH papers by Bui et al [3][4][5] on possible treatments for AH for the consultation. The neurologist agreed to try triptans as a preventative treatment for him, one pill of rizatriptan (regular tablet), 10 mg, 30 min before a flight.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The official insertion of AH in the international classification attracted the attention of the scientific community; subsequently and up until publication of this article, 45 publications in English on the topic have been published …”
Section: Historical Outlinementioning
confidence: 99%
“…Although the previously described peculiar clinical features of AH have been confirmed, the exact physiopathology remains uncertain. An experimental model, reproducing the one performed by Marchoux and Nepper in 1919, in which the characteristics of an airplane flight was simulated by entering a pressure chamber, while confirming the fundamental role played by the imbalance between sinusal and external air pressure, did not provide convincing explanation of the consequent headache . The authors reported high concentrations of cortisol in a group of 7 AH sufferers in comparison to 7 healthy controls, and thus proposed a possible role of anxiety.…”
Section: Historical Outlinementioning
confidence: 99%